Efektivitas Pembelajaran Fisika Berbantu Google Classroom sebagai Learning Management System (LMS) untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas XI SMA Negeri 1 Karangrayung - Juniati, Leni; Nuroso, Harto; Kurniawan, Affandi Faisal (Universitas PGRI Semarang, 2023)
This study aims to determine the effectiveness of learning physics assisted by Google Classroom as a Learning Management System (LMS) to improve critical thinking skills of class XI students of SMA Negeri 1 Karangrayung. This research is an experimental study with a Quasi Experimental Design, in the form of Non Equivalent Control Group Design. The population in this study were students of class XI IPA SMA Negeri 1 Karangrayung as many as 180 students. The sample used in this study were 2 classes totaling 72 students who were determined using the Cluster Random Sampling technique. The instrument used is a test instrument that has been adapted to indicators of critical thinking skills. Before the test instrument is used in research, the instrument has been validated and is suitable for use. The results of data analysis showed that there was an increase in students' critical thinking skills in the experimental class compared to the control class. This is evidenced by the average value of the experimental class 83.36 which is classified as very high, while the control class is 66.14 which is classified as moderate. In the right side t-test analysis, the results of are 10.606 1.147 and P 0.05, then is rejected and is accepted. This means that Google Classroom-assisted learning as a LMS is effective for improving critical thinking skills of class XI students of SMA Negeri 1 Karangrayung.Keywords: Critical Thinking Skill, Google Classroom, Learning Management System (LMS)